Community Perceptions and Attitudes in Management of the Mount Hamiding Protected Forest in North Halmahera Regency - Latupapua, Yosevita. Th.; Kailola, Jacob (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Mount Hamiding Protected Forest (HLGH) is administratively located in North Halmahera Regency and has a role in supporting living systems, regulating water management, preventing floods and seawater intrusion and increasing soil nutrients. The current condition of HLGH is experiencing damage due to human activities, namely forest encroachment, shifting cultivation and illegal logging. The research aims to determine community perceptions and attitudes in managing protected forests. This research was conducted in the HLGH area, taking place from July – November 2022. This research used a quantitative and descriptive qualitative approach. The parameters measured are community perceptions and attitudes in managing protected forests using a Likert scale. The results of the research show the perceptions and attitudes of the community in the six research locations, namely Roko village, perception value 26.95, attitude 11.97, Soakonora perception 27.36, attitude 11.87, Togawa perception 24.68, attitude 12.51, Mamuya Perception value is 26.78, attitude 11.47, Efi perception -Efi 27.18, attitude 12.17 and Wangongira perception 24.77, attitude 12.68. These findings illustrate that the perceived value in four villages is at a medium level, and two other villages are at a low level. The attitude of the six villages is in the medium category. This illustrates that people's perceptions and attitudes towards the existence, function and benefits of protected forests are still below standard. Thus, there is a need for outreach activities about the existence of protected forests and their functions and benefits to improve community perceptions and attitudes.